More than just luck: Innovation in humanitarian action - Obrecht, Alice; Warner, Alexandra T. (Humanitarian Innovation Fund, 2016)
In South Sudan, a new water treatment system that provides a community with more clean water at a lower cost. In Sierra Leone, a poster expl aining how to prevent the...